Fraport AG Frankfurt Airport Services Worldwide v. Republic of the Philippines: A Critical Analysis - Asriati Asriati; Muhammad Ilham Agus Salim (Jurnal Hukum dan Pembangunan Ekonomi, 2024)
Under ICSID arbitration related case of Fraport AG Frankfurt v. Philipphines have long been a focal point in discussions about the protection of foreign investment, state sovereignty and the enforceability of international arbitration decisions. This paper critically examines the implications of the case, focusing on the arbitral award’s reasoning, the concept of investor due diligence, and its broader consequences for international investment law that contextualize through comparisons with two other landmark cases: Saluka v. Czech (a successful claim) and Inceysa v. El Salvador (an unsuccessful claim). In Saluka, the tribunal upheld the claim of investor, emphasizing the host state's responsibility to ensure fairness and avoid arbitrary actions, even when legal complexities were involved. By contrast, in Inceysa, the tribunal rejected the investor's claim due to illegality in the investment's formation, aligning with the strict adherence to the legality principle seen in Fraport. However, the unique flaw in Fraport lies in the tribunal's failure to fully scrutinize the Philippines' complicity in enabling the investment despite its alleged non-compliance with domestic law. Unlike Saluka, which balanced investor protection with state sovereignty, or Inceysa, which rightfully penalized outright fraud, the Fraport decision rigidly applied the legality clause without considering the state's role in fostering ambiguity. This oversight diminished the case’s potential to address shared responsibilities and regulatory inconsistencies, which are crucial for a fair investment regime in evolving global markets.